Predictors of left ventricular systolic dysfunction after primary percutaneous coronary intervention for patients with left anterior descending artery occlusion - Mohamed E L Bordy; Ahmed Galal A Fattah Fahmy (Journal of Medicine in Scientific Research, 2021)
Background Depressed left ventricular (LV) systolic function after acute coronary syndrome is the most important predictor affecting morbidity and mortality. The primary objective of reperfusion therapy is to restore epicardial flow and to reperfuse the myocardial tissue. However, not all the patients show improvement, and a group of patients may experience depression in heart function. Aim To determine the factors affecting impairment of LV function assessed by echocardiography following successful primary percutaneous coronary intervention (PCI) in patients with acute coronary syndrome involving the left anterior descending (LAD) artery. Patients and methods A total of 50 patients were included in this study, who underwent primary PCI and stenting to LAD artery, as a culprit artery, and applying the inclusion and exclusion criteria, patients treated with the 1-stent technique were selected. Results The results of the current study showed that 34 patients had diabetes mellitus, 29 patients had hypertension, 31 patients had dyslipidemia, and 25 patients were smokers. Female percentage was 48% and male 52%, and the mean age was 57.2 ± 12.7 years. The factors that showed significant difference to predict LV systolic dysfunction were previous systolic dysfunction, multivessel disease, and thrombolysis in myocardial infarction (TIMI) flow after PCI. Conclusion We concluded that patient with myocardial infarction, preprocedural depressed LV systolic function, patient with multivessel disease, and those with postprocedural TIMI flow less than III were all predictive of depressed LV systolic function after primary PCI to LAD.